2020
DOI: 10.3928/01477447-20200827-01
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Dermatitis to Dermabond Prineo After Elective Orthopedic Surgery

Abstract: The Dermabond Prineo skin closure system (Ethicon, Somerville, New Jersey) is a wound closure device that combines a 2-octyl cyanoacrylate liquid adhesive and a self-adhesive polyester mesh. Although cyanoacrylates traditionally have been associated with low rates of sensitization, allergic contact dermatitis (ACD) to Dermabond products is being increasingly reported after orthopedic surgery. The authors describe the first case series of ACD to Dermabond Prineo where patch testing confirmed the diagnosis in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…However, it has been frequently reported that the constituents of Dermabond Prineo induce allergic reactions. These can lead to ACD or wound dehiscence and can cause critical complications such as deep SSI [ 10 , 25 , 27 29 , 34 37 , 39 42 ]. ACD is more likely to develop when the skin is in prolonged contact with the allergen or when the amount of allergen is high [ 36 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been frequently reported that the constituents of Dermabond Prineo induce allergic reactions. These can lead to ACD or wound dehiscence and can cause critical complications such as deep SSI [ 10 , 25 , 27 29 , 34 37 , 39 42 ]. ACD is more likely to develop when the skin is in prolonged contact with the allergen or when the amount of allergen is high [ 36 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is still no established method for the prophylaxis of ACD after the use of Dermabond Prineo. According to previous reports, patch testing for Dermabond Prineo glue or polyester mesh has been known to be useful to identify the patient who may have allergenic reactions postoperatively [ 29 ]. Bulky occlusive dressings after TAA can increase the absorption of allergens, and water or a humid environment can cause depolymerization to create a strong sensitizer, a monomer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported a case series of ACD to Dermabond ® Prineo ® from Perth, where all six cases were patch tested, confirming the diagnosis of ACD to Dermabond Prineo ® . 3 Four had prior exposure to Dermabond ® Prineo ® , one to Dermabond ® liquid adhesive and one had no known exposure to Dermabond ® products. In our series, ACD sometimes caused prolonged hospitalization It is imperative to convey to all healthcare professionals using Dermabond ® Prineo ® that development of ACD may occur following its use, particularly in patients who have been exposed to it before.…”
Section: Main Textmentioning
confidence: 99%